Derivation of Nanocellulose from Native Rice Husk (Chemical Engineering Research Bulletin, 2018)
Nanocellulose has been in numerous applications and can be obtained from bioresources. This work demonstrates the derivation of nanocellulose from an alternative option i.e. rice husk. The processed rice husk was refined by chemical and mechanical treatments. Nanocellulose was subsequently derived from the refined rice husk through acid hydrolysis followed by centrifugation, dialysis and ultrasonic treatment. Scanning Electron Microscopy ensured the nanoscale diameter while Fourier Transformed InfraRed Spectroscopy confirmed the removal of noncellulosic materials. It is therefore proposed that the native rice husk can also be utilized for manufacturing nanocellulose reducing its adverse environmental impacts.Chemical Engineering Research Bulletin 20(2018) 19-22